The Role of Cellular Prion Protein in Cancer Biology: A Potential Therapeutic Target - Ding, Manqiu; Chen, Yongqiang; Lang, Yue; Cui, Li (Frontiers in Oncology, 2021)
Prion protein has two isoforms including cellular prion protein (PrPC) and scrapie prion protein (PrPSc). PrPSc is the pathological aggregated form of prion protein and it plays an important role in neurodegenerative diseases. PrPC is a glycosylphosphatidylinositol (GPI)-anchored protein that can attach to a membrane. Its expression begins at embryogenesis and reaches the highest level in adulthood. PrPC is expressed in the neurons of the nervous system as well as other peripheral organs. Studies in recent years have disclosed the involvement of PrPC in various aspects of cancer biology. In this review, we provide an overview of the current understanding of the roles of PrPC in proliferation, cell survival, invasion/metastasis, and stem cells of cancer cells, as well as its role as a potential therapeutic target.